RASM USMANI DALAM PENULISAN AL-QUR’AN BRAILLE - Jaeni, Ahmad (SUHUF, 2017)
This article presents a study of the effort of writing the Braille Qur’an in Indonesia which uses rasm usmani amid the trend of writing the Braille Quran in the Islamic world that still uses rasm imlai. The use of rasm usmani in the writing of the Braille Qur’an is still considered by some practisioners as not possible yet. The reason is that besides the difference in character between Arabic script and Braille symbol, the application of rasm usmani is considered to make a difficult for its users. On the other hand, the consensus of the majority of scholars state that the writing of the Qur’an with rasm usmani is a necessary. Based on the results of the study of the Braille Qur’an of Indonesian Standard, in fact the writing of the Braille Qur’an with rasm usmani can be done by using a selective adaptation model, i.e. the application of rasm usmani is done as long as it can be adapted into the writing system of the Braille Qur’an and the result is not difficult for the user.